Notes on the Council of Ferrara-Florence Preserved in Georgian Manuscripts - Megeneishvili, Nino (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2019)
It is a fact that the Council of Florence was the most important event not only for the Christian world but also for Georgia. It changed the world order and influenced Georgian reality and literary life. Manuscripts reflecting the above-mentioned Council of FerraraFlorence are preserved in Georgian National Center for Manuscripts. These manuscripts are of anti-Catholic polemical character and are dated by the XVIII century. First of all, we should mention the literary work “The Council of Florence” two copies of which are preserved: 1. A1443 and 2. Q-1391. As maintained by Besarion Orbelishvili, his work is a response to the decisions made by the Council. Thus Besarion does not describe the details of the Council, but the content. B.Orbelishvili’s “Grdemli” is an anti-Catholic polemical literary work and treaty. It is the political and social literary product of the XVIII century. “Mzametkveleba” by Anton, Catholicos of Georgia is the continuation of “Grdemli”. Here, chapter 3, passage 17 is about the response of Latins. Anton Catholics also starts and finishes anti-Catholic polemical part of “Mzametkveleba” with the overview of the Council of Florence.